ERNICA Consensus Conference on the Management of Patients with Esophageal Atresia and Tracheoesophageal Fistula: Follow-up and Framework - Dingemann, Carmen; Eaton, Simon; Aksnes, Gunnar; Bagolan, Pietro; Cross, Kate M.; De Coppi, Paolo; Fruithof, JoAnne; Gamba, Piergiorgio; Husby, Steffen; Koivusalo, Antti; Rasmussen, Lars; Sfeir, Rony; Slater, Graham; Svensson, Jan F.; Van der Zee, David C.; Wessel, Lucas M.; Widenmann-Grolig, Anke; Wijnen, Rene; Ure, Benno M. (European Journal of Pediatric Surgery, 2019)
Introduction Improvements in care of patients with esophageal atresia (EA) and tracheoesophageal fistula (TEF) have shifted the focus from mortality to morbidity and quality-of-life. Long-term follow-up is essential, but evidence is limited and standardized protocols are scarce. Nineteen representatives of the European Reference Network for Rare Inherited Congenital Anomalies (ERNICA) from nine European countries conducted a consensus conference on the surgical management of EA/TEF.Materials and Methods The conference was prepared by item generation (including items of surgical relevance from the European Society for Pediatric Gastroenterology Hepatology and Nutrition (ESPGHAN)-The North American Society for Pediatric Gastroenterology, Hepatology and Nutrition (NASPGHAN) guidelines on follow-up after EA repair), item prioritization, formulation of a final list containing the domains Follow-up and Framework, and literature review. Anonymous voting was conducted via an internet-based system. Consensus was defined as ≥75% of those voting with scores of 6 to 9.Results Twenty-five items were generated in the domain Follow-up of which 17 (68%) matched with corresponding ESPGHAN-NASPGHAN statements. Complete consensus (100%) was achieved on seven items (28%), such as the necessity of an interdisciplinary follow-up program. Consensus ≥75% was achieved on 18 items (72%), such as potential indications for fundoplication. There was an 82% concordance with the ESPGHAN-NASPGHAN recommendations. Four items were generated in the domain Framework, and complete consensus was achieved on all these items.Conclusion Participants of the first ERNICA conference reached significant consensus on the follow-up of patients with EA/TEF who undergo primary anastomosis. Fundamental statements regarding centralization, multidisciplinary approach, and involvement of patient organizations were formulated. These consensus statements will provide the cornerstone for uniform treatment protocols and resultant optimized patient care.
Keywords: esophageal atresia with tracheoesophageal fistula; pediatric surgery; follow-up; management; consensus conference